Pengaruh Kualitas Pelayanan terhadap Kepuasan Konsumen: (Studi Kasus pada Cafe Alas Klotok Kediri) - Semuelson Wonda; Yogi Yunanto; Endang Triwidyati (AKUNTANSI 45, 2026)
This study aims to analyze the effect of service quality on consumer satisfaction at Cafe Alas Klotok Kediri. The research employs a quantitative approach, with data collected through structured questionnaires completed by 50 respondents who regularly visit the café. The study examines the impact of five dimensions of service quality tangibles, reliability, responsiveness, assurance, and empathy on overall consumer satisfaction. Data analysis was conducted using partial t-tests and simultaneous F-tests to determine the influence of each dimension individually as well as the combined effect. The results indicate that, individually, reliability (sig. 0.003), assurance (sig. 0.005), and empathy (sig. 0.003) significantly influence consumer satisfaction, demonstrating that these aspects are crucial for customers’ perceived quality. In contrast, tangibles (sig. 0.050) and responsiveness (sig. 0.073) were found to have no significant effect. Simultaneously, overall service quality has a significant impact on consumer satisfaction (sig. 0.008), suggesting that comprehensive attention to service factors is necessary. These findings provide practical insights for the management of Cafe Alas Klotok Kediri to strategically enhance service quality and foster higher levels of customer satisfaction and loyalty.